PENGARUH KEBIJAKAN TAX AMNESTY, KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA MANADO - Rorong, Elisabeth Nadia; Kalangi, Lintje; Runtu, Treesje (Universitas Sam Ratulangi, 2017)
The purpose of this study is to analyze the effect of tax amnesty policy, taxpayer awareness and tax sanctions on taxpayer compliance of individuals in KPP Pratama Manado. The Population in this study is all Individual Taxpayers registered pursuant to tax amnesty policy in KPP Pratama Manado. The number of samples in this study were 30 respondents in Manado area. Sampling was done by using Purposive Sampling Method. Methods Data analysis used in this research is validity test, reliability test, classical assumption test, multiple regression analysis, determination coefficient (R2 test), regression test (F test), and partial regression test (t test). Based on the results of data analysis, it is known that tax amnesty has a positive effect on taxpayer compliance. Result of t test show value t count 3,956> t table 1,708 with significance value (0,01) <0,05 so that H1 accepted. Awareness of taxpayers does not significantly affect taxpayer compliance. The result of t test shows t value (-790) <t table 1,708 with significance value (0,437)> 0,05 so that H2 is rejected. Tax sanctions have no positive effect on taxpayer compliance. The result of t test shows t value (-2,167) <t table 1,708 with significance value (0,04) <0,05 so that H3 is rejected. Variable tax amnesty, taxpayer awareness and tax sanction can be used to explain compliance of taxpayers by 45%. Keywords: tax amnesty, taxpayer awareness, tax sanction, and taxpayer compliance